ESTEREOTIPOS DE GÉNERO Y CIBERBULLYING EN LAS SERIES DE FICCIÓN ADOLESCENTES: UN ANÁLISIS COMPARATIVO DE GOSSIP GIRL, PRETTY LITTLE LIARS Y GET EVEN - Dra. Noemí MOREJÓN LLAMAS, (Fonseca, Journal of Communication, 2023)
Teen fiction series act as important socializing agents. The female stereotypes represented in them have the power to reconfigure the viewers’ identity construction, who will assume certain roles and apply them to their reality. This paper, which identifies a slow and superficial change in series aimed at adults (through Content Analysis and Critical Discourse Analysis (CDA)), analyzes female stereotypes and their relationtship with cyberbullying in series such as Gossip Girl, Pretty Little Liars and Get Even.